Current status of the management and outcomes of acute aortic dissection in Japan: Analyses of nationwide Japanese Registry of All Cardiac and Vascular Diseases-Diagnostic Procedure Combination data. Issue 3 (1st October 2020) - Yamaguchi, Tetsuo; Nakai, Michikazu; Sumita, Yoko; Miyamoto, Yoshihiro; Matsuda, Hitoshi; Inoue, Yousuke; Yoshino, Hideaki; Okita, Yutaka; Minatoya, Kenji; Ueda, Yuichi; Ogino, Hitoshi
Abstract : Background: Despite recent advances in the diagnosis and management, the mortality of acute aortic dissection remains high. This study aims to clarify the current status of the management and outcome of acute aortic dissection in Japan. Methods: A total of 18, 348 patients with acute aortic dissection (type A: 10, 131, type B: 8217) in the Japanese Registry of All Cardiac and Vascular Diseases database between April 2012–March 2015 were studied. Characteristics, clinical presentation, management, and in-hospital outcomes were analyzed. Results: Seasonal onset variation (autumn- and winter-dominant) was found in both types. More than 90% of patients underwent computed tomography for primary diagnosis. The overall in-hospital mortality of types A and B was 24.3% and 4.5%, respectively. The mortality in type A patients managed surgically was significantly lower than in those not receiving surgery (11.8% (799/6788) vs 49.7% (1663/3343); p <0.001). The number of cases managed endovascularly in type B increased 2.2-fold during the period, and although not statistically significant, the mortality gradually decreased (5.2% to 4.1%, p =0.49). Type A showed significantly longer length of hospitalization (median 28 days) and more than five times higher medical costs (6.26 million Japanese yen) than those in type B. The mean Barthel index at discharge was favorable in both type A (89.0±22.6) and type B (92.6±19.0). More than two-thirds of type A patients and nearly 90% of type B patients were directly discharged home. Conclusions: This nationwide study elucidated the clinical features and outcomes in contemporary patients with acute aortic dissections in real-world clinical practice in Japan.